Characterization of Taxable Units and Tax Bases under the Income Tax Schedules of Schedule ‘A’ and ‘B’ of the Federal Income Tax Proclamation of Ethiopia: A Commentary - Addis, Belete (Bahir Dar University Journal of Law, 2023)
The income tax structure of Ethiopia is substantively schedular. The Federal Income Tax Proclamation incorporates five income tax Schedules (Schedule ‘A’, ‘B’, ‘C’, ‘D’ and ‘E’). The first four provide their own taxable unit and tax base, the basic two elements which determine the scope of any income tax schedule. The last Schedule, on the other hand, is all about exemptions. This paper aims to briefly overview the income tax schedules and most importantly to examine how taxable units and tax bases are characterized under the first two Schedules. In doing so, an assessment is also made on the developments and gaps of the current income tax regime. The paper uses a doctrinal legal research method and based on the critical analysis of relevant legislations and literatures, it is found that the current income tax regime unveils some developments such as incorporating informative definitional provisions. However, the regime still suffers from shortcomings, such as characterization overlaps and clarity problems with potential administrative difficulties. To curb these, the paper among other things, calls for the enactment of directives or advance rulings.